The Phenomenon of Ambivalence in Policy Implementation: How Muhammadiyah Universities Protect Women against Sexual Violence - Angin, Ria; Fauziah, Fauziah; Haerah, Kahar (Universitas Muhammadiyah Tangerang, 2024)
This article discusses